2009
DOI: 10.1186/1475-2867-9-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PI3K increases oxaliplatin sensitivity in cholangiocarcinoma cells

Abstract: Background: Resistance of cholangiocarcinoma to chemotherapy is a major problem in cancer treatment. The mechanism of resistance is believed to involve phosphoinositide-3-kinase (PI3K)/ Akt activation. Although the platinum-containing compound oxaliplatin has been extensively used in the treatment of several solid tumors, recent data regarding its use to treat cholangiocarcinoma are ambiguous. Oxaliplatin resistance in this disease could potentially involve PI3K pathways. We, therefore, examined the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 21 publications
3
30
0
Order By: Relevance
“…Western blot analyses were performed as previously described (Leelawat et al 2009). The blots were Wrst probed with antibodies against phospho-Akt, phospho-p38 MAPK and MKP-1 and then reprobed with antibodies against total Akt, p38 MAPK and -tubulin.…”
Section: Western Blotting Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot analyses were performed as previously described (Leelawat et al 2009). The blots were Wrst probed with antibodies against phospho-Akt, phospho-p38 MAPK and MKP-1 and then reprobed with antibodies against total Akt, p38 MAPK and -tubulin.…”
Section: Western Blotting Analysismentioning
confidence: 99%
“…Previously, we also demonstrated that PI3K is constitutively activated in KKU-100 cells. However, treating the KKU-100 cells with LY294002 (a speciWc inhibitor of PI3K) does not inhibit the proliferation of these cells (Leelawat et al 2009). Therefore, in this study we aimed to elucidate the mechanism by which KKU-100 cells resist PI3K inhibition.…”
Section: Introductionmentioning
confidence: 98%
“…It could have synergistic effect with chemotherapy drugs. It has been demonstrated in cholangiocarcinoma cells, the inhibition of PI3K increased oxaliplatin cytotoxicity [Leelawat et al, 2009]. In colon cancer, inhibition of PI3K has also been shown to increase the cytotoxicity of low dose of BBR3610 [Mitchell et al, 2007].…”
Section: Therapeutic Implicationsmentioning
confidence: 98%
“…Furthermore, sorafenib-released media was used to test whether sorafenib maintained its biological activity during the stent-coating process and drug-release experiment. At 1,5,10,15,20, and 30 days of the drug-release experiment, the collected media were used to test anticancer activity.…”
Section: In Vitro Release Studiesmentioning
confidence: 99%
“…1 reported with combinations of anticancer drugs. [4][5][6][7][8][9] Among them, clinical trials with a combination of gemcitabine plus cisplatin were reported to have significant survival advantage compared to gemcitabine alone.…”
Section: Introductionmentioning
confidence: 99%